2005
DOI: 10.1073/pnas.0500634102
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of liver X receptor β leads to adult-onset motor neuron degeneration in male mice

Abstract: Male mice with inactivated liver X receptor (LXR) β suffer from adult-onset motor neuron degeneration. By 7 months of age, motor coordination is impaired, and this condition is associated with lipid accumulation and loss of motor neurons in the spinal cord, together with axonal atrophy and astrogliosis. Several of these features are reminiscent of the neuropathological signs of chronic motor neuron disease such as amyotrophic lateral sclerosis. Because the LXRs are important for cholesterol and lipid metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
107
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 54 publications
2
107
0
Order By: Relevance
“…These observations suggest that LXRβ may be protective against neurodegeneration of substantia nigra (25). Furthermore, there is activation of microglia in the substantia nigra of aging LXRβ −/− mice, and this suggests that LXR may have immunosuppressive effects in the brain (26) as it does in the rest of the immune system.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These observations suggest that LXRβ may be protective against neurodegeneration of substantia nigra (25). Furthermore, there is activation of microglia in the substantia nigra of aging LXRβ −/− mice, and this suggests that LXR may have immunosuppressive effects in the brain (26) as it does in the rest of the immune system.…”
Section: Discussionmentioning
confidence: 89%
“…We have previously shown that LXRβ expression is involved in formation of superficial cortical layers and migration of later-born neurons in embryonic mice (23,24), and that LXRβ is essential for maintenance of motor neurons in the spinal cord and dopaminergic neurons in the substantia nigra (25,26). The substantia nigra and motor neurons in the spinal cords of LXRβ −/− mice are normal until the mice are 6 mo of age.…”
mentioning
confidence: 99%
“…In the lateroventral horns of L1 segments of the spinal cord, the number of motor neurons was evaluated by counting large Nissl-staining motor neurons of 35-50 m. Cell counts were made within an area demarcated by a horizontal line drawn through the central canal and encompassing the ventral horn of the gray matter and at least 15-20 slides were counted per spinal cord specimen (32). Mean counts for each group were compared by Student's t test.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, when only LXR␤ is inactivated (LXR␤ Ϫ/Ϫ mice), by 6 months of age, there is motor dysfunction that progresses with age into hind limb paralysis (32). Concomitant with worsening motor dysfunction with age is a degeneration of the large ␣-motor neurons in the ventral horn of the spinal cord similar to what is seen in ALS.…”
mentioning
confidence: 99%
“…Ligand activation of LXRs promotes cholesterol efflux from glia (12,13) and primary neurons (14), whereas mice deficient in expression of Lxr␣ and Lxr␤ develop marked accumulation of neutral lipids in the brain (15). Functionally, loss of LXR␤ leads to adult-onset motor neuron degeneration by the age of 7 months (16). The role of LXRs in human neurodegenerative diseases, however, remains largely unknown.…”
mentioning
confidence: 99%